Students’ Perception of Using ELSA Speak to Improve Pronunciation Skills - Mauralia, Risti Raffa; Musdizal, Musdizal (Journal of English Language and Education, 2025)
Pronunciation is crucial while learning English, yet many students struggle to get it right. ELSA Speak and other language learning applications offer self-paced, artificial intelligence-powered pronunciation at one of the Islamic institutes in Jambi. A qualitative descriptive approach was utilized, interviewing five pupils. The findings show that users valued the app’s real-time feedback and phonetic comparison capabilities, which helped them, discover and correct pronunciation mistakes. While most students felt more secure speaking informally, confidence in formal circumstances remained low due to chronic worry. Despite technical limitations, such as problems detecting particular vowel sounds, users considered the app helpful in constantly practicing pronunciation. The study finds that ELSA Speak effective in boosting pronunciation, while other treatments may be needed to address speaking anxiety in formal situations.